The Extent of Fieldwork Application in the Teaching of Geography in Federal Universities in Nigeria - Emiola, Adetoun Gladys (NIU Journal of Social Sciences, 2018)
Fieldwork in geography is an inseparable, unalienable and cooperate part of the teaching and learning process. When viewed from the nature and content of geography which makes continuous reference to space and spatial features, the field outside the classroom inevitably remains the only true laboratory for carrying out geographical experiments as well as observation in teaching and learning. Be that as it may, several factors, have largely and grossly under applied the use of fieldwork in teaching geography in Nigerian Federal universities. Hence there is the need to assess the extent of use of fieldwork as a method of teaching geography in Nigerian federal universities. To carry out this research, four research questions were raised, and four major objectives posed. This study is of significant relevance to the government, curriculum developers, geography lecturers and geography students in various federal universities in Nigeria. The theoretical framework for the study was based on Kolb’s theory of Experiential Learning. The study viewed various literature and works of prominent geographers and social scientists who have ventured into the germane but neglected concept of fieldwork application in teaching geography. Teachers and students questionnaire were the research instruments utilized in this study, while stratified random sampling method was used to select the sample size. Consequently, a sample size of 109 respondents comprising of 100 students and 9 lecturers was used in this study. Descriptive survey design was used in the analysis of the results. Several critical findings and recommendations were made. Keywords: fieldwork, federal universities, teaching, experiential learning.